Congress Proceedings: Sixth Annual Congress, 6-8 April 1983 (Book). - Hendrickson, Harvey S.; Chang, Lucia S. (The Accounting Review, 1985)
Reviews the book "Congress Proceedings: Sixth Annual Congress, 6-8 April 1983."